Employers' Assessment of Competences of the Employees of the Shipbuilding, Forestry and Fishing Industries of the Arkhangelsk Oblast in the Context of the Development of Digitalization and Automation of Production - Aleksandr A. Saburov; Aleksey S. Nikiforov; Oleg V. Minchuk (Арктика и Север, 2023)
The article is devoted to the study of employers’ perceptions of the competences of employees in the shipbuilding, fishing and forestry industries of the Arkhangelsk Oblast in the context of digitalization and automation of production. As part of the sociological research, the team conducted a questionnaire survey and semi-structured interviews among representatives of enterprises in these industries. The results of the research allowed drawing conclusions that the professional competencies of employees, as well as abilities to work independently, in non-standard situations and under stress are currently the most in demand for employers. There is also a very high demand for qualities associated with discipline and the desire to develop in the profession. In terms of the size of enterprises, the higher requirement for almost all competences in small and medium-sized enterprises compared to large employers is noteworthy. The authors conclude that about half of the enterprises in the shipbuilding, forestry and fishing industries of the Arkhangelsk Oblast have implemented automation and digitalization into all key production processes. In the near future, more than 50% of employers expect a high demand for employee competencies related to the use of new production technologies. The survey revealed a gap between employers’ expectations and the actual level of professional training and skills of recent graduates of educational institutions of higher and secondary vocational education, including with regard to the most in-demand knowledge, skills and abilities. In the context of industries, it is noteworthy that the level of satisfaction with the training of graduates of shipbuilding industry is much lower, except for those who received education through the “Plant-University” system (Severodvinsk).